Structural-semantic analysis: a method towards a classification of Malaysian folktale / Harryizman Harun and Zulikha Jamaludin - Harun, Harryizman; Jamaludin, Zulikha (Division of Research and Industry Linkages , UiTM Melaka, 2014)
This paper expounds a method that will be used in a study to propose a Malaysian folktale classification system focusing on Malay folktales. At core, there are three significant folktale classification systems that classify based on three different folktale units: type, motif, and function. Individually, type and motif each classifies based on content of folktale whereas function, structure of folktale. The study intends to generate the folktale classification system for the Malay folktales based on an integration of the three distinguished units of the folktale classification system. In order to achieve that, the method opted is structural-semantic analysis. The method, which constitutes of three levels of classification classifies sequentially according to the content and the structure of the Malay folktales. It is hoped that the method adapted would engender a holistic and robust Malaysian folktale classification system.